2013
DOI: 10.4304/jcp.8.7.1815-1820
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Haptic and Visual Training Method of Learning Chinese Handwriting with a Haptic Guidance

Abstract: International audienceIn this paper a use of haptic and visual training for Chinese handwriting learning is investigated. Participants learned a given character under three training conditions (haptic, visual, haptic-visual) and were required to write the given character plus two characters with common stokes on a tablet before and after training for improvement comparison. Performance was measured in terms of mean speed, inair time, size, order, and shape. Findings from this study indicate that visual informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Results of spatial error supports the finding that spatial information is mainly perceived visually (Welch and Warren, 1980 ; Nesbitt, 2003 ). In literature, comparable studies showed that addition of reactive haptic feedback for a complex rowing (Sigrist et al, 2015 ), path control feedback for a 2D shape drawing (Yang et al, 2008 ) and haptic guidance in Chinese handwriting (Xiong et al, 2013 ) tasks did not result in a significantly better learning than visual alone in the delayed retention tests. In our study, participants did not receive any haptic feedback during the training sessions.…”
Section: Discussionmentioning
confidence: 95%
“…Results of spatial error supports the finding that spatial information is mainly perceived visually (Welch and Warren, 1980 ; Nesbitt, 2003 ). In literature, comparable studies showed that addition of reactive haptic feedback for a complex rowing (Sigrist et al, 2015 ), path control feedback for a 2D shape drawing (Yang et al, 2008 ) and haptic guidance in Chinese handwriting (Xiong et al, 2013 ) tasks did not result in a significantly better learning than visual alone in the delayed retention tests. In our study, participants did not receive any haptic feedback during the training sessions.…”
Section: Discussionmentioning
confidence: 95%
“…They could even be traced on the monitor on which they were presented. In a pilot study of practicing Chinese characters with observation of a teacher, haptic guidance in accordance with the movements of the teacher, and visuo-haptic demonstration, Xiong et al (2013) concluded that visual information facilitated the learning of the 38 shape of the practiced letter, but there was no benefit of haptic guidance for dynamic characteristics. Rather haptic guidance seemed to facilitate transfer of practice to new letters which shared strokes with the practiced letter.…”
Section: Contrasting the Effects Of Haptic Guidance On Spatial And Dymentioning
confidence: 97%
“…Recent technological developments, particularly in haptics and robotics, have allowed researchers to embed novel and complex feedback presentations into training programs. Robotic training and haptics-enhanced performance are being explored in fields, such as neurorehabilitation (Kahn et al, 2006; Huang et al, 2009), surgical training (Prasad et al, 2002; Delorme et al, 2012), handwriting instruction (Vishnoi et al, 2009; Kim et al, 2013; Xiong et al, 2013), and sports training (Huang et al, 2011). The most common form of robotic or haptic training is haptic guidance; however, the term is used to refer to a variety of training strategies (Williams and Carnahan, 2014), including that which delivers forces, or assistance, on the basis of movement-induced feedback about performance (Bluteau et al, 2008; Marchal-Crespo and Reinkensmeyer, 2008; Lee and Choi, 2010; Marchal-Crespo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%